EXPLORING THE INFLUENCE OF HEADMASTER LEADERSHIP ON TEACHER PERFORMANCE AT MI AL-KARIM: MEDIATION BY WORK MOTIVATION AND ORGANIZATION CLIMATE - Muchammad Imam Chambali; Edy Sulistiyawan; Moch. Munir Rahman (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to examine the influence of democratic leadership style, work motivation, and organization climate on teacher performance at MI Al-Karim Surabaya. The research method used is Structural Equation Modeling (SEM) with Partial Least Squares (PLS) as the data analysis tool. Data collection was conducted through questionnaires distributed to 41 teachers at MI Al-Karim Surabaya. The results of the analysis show that democratic leadership style has a positive effect on teachers' work motivation and organization climate. However, democratic leadership style does not have a direct effect on teacher performance. Work motivation also does not have a direct effect on teacher performance, but organization climate has a positive effect on teacher performance. Additionally, organization climate mediates the relationship between democratic leadership style and teacher performance.